The KPK'S Investigation Termination Warrant (SP3) Authority: Endeavours To Prevent Abuse Of Power - Mohammad Syaiful Aris; Auly Nahdyan; Bagus Oktafian Abrianto (Arena Hukum)
The Corruption Eradication Commission (KPK) is a state entity created under Law No. 30 of 2002 in Indonesia to support the prosecutor’s office and the police in combating corruption. Law No. 30 of 2002 has been subject to multiple judicial reviews by the Constitutional Court (MK). In 2019, a proposal was submitted to amend Law No. 30 of 2002. The modification of the Law has both advantages and disadvantages, with some viewing it as weakening the KPK by categorising it inside the executive branch, thereby impacting the agency’s independence. One of the main focuses of this Article is the authorisation of the KPK to issue a Warrant to Terminate Investigation (SP3). SP3 results from the legal principle of defending human rights and serves as a tool for checks and balances, but it can also be prone to misuse. The research focuses on two main issues: changes in the KPK’s authority and the KPK Institution’s deconstruction. Secondly, the consequences of the KPK issuing SP3 and the risk of authority misuse in combating corruption. This study involves legal research utilising both statutory and conceptual approaches. This paper intends to evaluate the various ways in which power abuse might occur within a corruption eradication system, specifically focusing on delegating authority to the KPK in issuing SP3 from a constitutional standpoint. The conclusions of this study provide a way to prevent the abuse of SP3 through reporting procedures and case titles at the KPK Supervisory Board (Dewas). In addition, the method should include authorising the KPK to revoke SP3.